Determination of Antioxidant Composition in Berry Juices Using Solid Phase Extraction with Copper Phthalocyanine - Faustova Zhanna V.; Slizhov G.; Gavrilenko M. A. Mikhail Alekseevich; Gavrilenko N. A. Natalia Airatovna; Terentiev R. A. R. A. (2015, 2015)
Title screen